Blood trace pattern analysis contributes to reveal feigned heist Blutspurenmusteranalyse trägt zur Aufklärung eines vorgetäuschten Raubüberfalls bei - Bützler, I. M.; Rothschild, M. A.; Kamphausen, T. (Rechtsmedizin, 2021)
A man was found injured with a cut on the left side of his neck and unconscious on the floor of his garage. He reported being attacked from behind, robbed and injured with a sharp instrument. During the analysis of the blood trace pattern doubts arose if the story of the man was true and a self-inflicted injury could be considered. If the course of events is reconstructed on the basis of blood traces, the incident did not take place at one place. In a niche a carpet knife was found hidden in an oil canister. After extensive investigations a suspect was exonerated and the injured person was sentenced for feigning the commission of a crime.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Physical examination; Plausibility testing; Self-injury; Sharp force; Unconsciousness